PERSPEKTIF SOSIOLOGIS PERLINDUNGAN ANAK PELAKU TINDAK PIDANA BERBASIS RESTORATIVE JUSTICE - Aldeka Putra, Atra; Suryadi; Siti Zuliyah (LPPM, Universitas Muhammadiyah Riau, 2023)
Children are assets of the country that must be preserved, thus their rights must be upheld even if they commit crimes. The effect of their social environment, including their peers, community, and parenting practices, cannot be isolated from children's criminal behavior. The state must be present to protect children because punishment will have a detrimental effect on their mental and physical development. Through Law Number 11 of 2012 Concerning the Juvenile Criminal Justice System, the state has created space to offer special protection to children who commit crimes. Under this law, criminal issues committed by children are resolved through a restorative justice process. What is the sociological perspective on the protection of children who commit crimes from a restorative justice perspective, then, when looking at these issues? In order to examine the truth and reality of the laws that are in place in society with relation to the sociological perspective of defending children from criminal acts based on restorative justice, the research technique used is sociological juridical. According to the study's findings, the prevalence of restorative justice in laws and regulations demonstrates the sociological influence of the process, which includes social control, social services, and accountability to victims and society.